The Use of English Language Learning Videos Designed Through Canva App: Students’ Perceptions - Ilyas, Muhammad; Hermawati Syarif; Refnaldi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Recordings are exceptionally good at passing on the teacher’s eagerness and objectives for teaching English, which are difficult to clarify. It can be passed on within the video. The teacher used to get the learning videos from YouTube or Facebook. Utilizing these learning videos makes lessons more curious within the classroom. Communication and innovation can be used as curious and fun media. Remembering that in the current circumstance, learning can be worn out both online and offline, at that point, the teachers must be able to create learning media by utilizing ICT. Teachers must also be able to create inventive and imaginative learning videos that integrate ICT. One method for making videos was to use the Canva app. This study was considered a means of sharing information about students’ perceived ease of use and convenience when using English learning recordings coordinated with the Canva app. It made it less difficult for them to comprehend the English material because of its numerous highlights, which made learning movement more enjoyable. It also helped make the course more appealing to the teachers and students. The students then shared their thoughts on how simple it was to obtain the English material by utilizing it.